Towards experiments on a superconducting atom chip. - Wu, Xing. (2009)
This thesis widely reviews the literatures on laser cooling and trapping, magnetic trapping and atom chip. Temperatures and atom number densities of 87-Rubidium cloud in our magneto-optical trap, compressed magneto-optical trap and molasses experiments are reported. For `Z' traps with wires of width-to-thickness ratio = 500, discrepancy in the magnetic field distribution from those of `Z' wires at much more moderate widthto-thickness ratio during the compressing stage is discovered through simulations with Finite Element Method. Offset magnetic field has to be reduced in order to recover the normal feature of a `Z' trap during the compressing stage. The thermally induced atom spin flip lifetime in our `Z' trap is also approximated. The design of a cold finger structure which can enhance the cooling of a YBCO superconducting atom chip inside a liquid nitrogen cryostat to below critical temperature is summarized. The distortion to the magnetic quadrupole trap due to the eddy current inside a nearby chip holder at liquid nitrogen temperature during the fast switching of the trap is investigated.